Understanding the impact of European asylum and migration policies: A promise of a dignified life - Felix, Claire (2022)
The 2015-refugee crisis fully hit Greece after years of strict austerity, challenging notions of entitlement, the role of institutions, and overall assumptions on migration. This article examines Greek asylum and migration policies and their impact on the every-day life of asylum seekers. Drawing on Foucauldian perspectives and fieldwork in Eleonas camp in Athens and Moria camp in Lesvos, it identifies the main consequences of those measures. Results show that policies are exclusionist and perpetuate irregularity and illegality. Finally, it takes the debate to a macro-level, challenging the responsibility of the European Union